2003
DOI: 10.1192/bjp.182.3.233
|View full text |Cite
|
Sign up to set email alerts
|

Disintegration of the components of language as the path to a revision of Bleuler's and Schneider's concepts of schizophrenia

Abstract: Evaluating the features of psychosis as deviations in the cerebral organisation of language paves the way to a concept of psychosis that supersedes these traditional but competing categorical concepts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 15 publications
0
28
1
1
Order By: Relevance
“…On these tasks, the patients with FRS actually tended to perform better than the FRS-ones. Overall, we do not replicate the findings of language disturbances in FRS [26,28] . Indeed the current results are consistent with those reported by Verdoux et al [27] , indicating an advantage for FRS+ patients in language abilities.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…On these tasks, the patients with FRS actually tended to perform better than the FRS-ones. Overall, we do not replicate the findings of language disturbances in FRS [26,28] . Indeed the current results are consistent with those reported by Verdoux et al [27] , indicating an advantage for FRS+ patients in language abilities.…”
Section: Discussioncontrasting
confidence: 55%
“…Another proposed test of this hypothesis involves examination of speech disturbances. In 2 separate studies, Ceccherini-Nelli et al [26] and CeccheriniNelli and Crow [28] reported positive correlations between FRS scores and factor scores on the Clinical Language Disorder Rating Scale. However, Verdoux et al [27] showed that higher FRS scores were associated with less impairment on another language scale, providing contrary findings for the proposal of language dis turbances in FRS.…”
Section: Introductionmentioning
confidence: 99%
“…According to language disturbances in schizophrenia, delateralisation might be a good explanation for a lower incidence of schizophrenia within a population growing older, whereas there is a peak of incidence at the age of 15-30 years (Möller, Laux, & Kapfhammer, 2005). Probably, failure of lateralisation in the young (Ceccherini-Nelli & Crow, 2003) causes a maximum of hemispheric confusion which, in combination with prenatal trauma (Brown, 2006), genetic predisposition (chapter 3) and subcortical-cortical dysfunction (chapter 5) may lead to psychotic symptoms. As shown by our own data, elderly individuals are familiar with using right hemispheric language areas which might be one explanation for the early and quite age-specific onset of schizophrenia.…”
Section: Brain Asymmetry and Language-lateralisationmentioning
confidence: 99%
“…CLANG segregates language abnormalities into three empirically validated levels: syntactic (syntactic abnormalities, including phonetic abnormalities and abnormal word choice), semantic (corresponding to the traditional idea of loose associations) and production (corresponding to the notion of poverty of speech) (Chen et al, 1996). Using CLANG to assess linguistic deviations, Ceccherini-Nelli and Crow (2003) also found a three factor structure, namely 'semantic', 'poverty', and 'excess'. This overlapped Chen et al (1996)'s structure on the semantic and production/poverty factors.…”
Section: Introductionmentioning
confidence: 99%